Assessing the Equity of Educational Access in the Prabowo Administration Era: Policy Analysis and Alternative Solutions Toward Inclusive Education in Indonesia - Dwi Pangga; Ketut Suma; I Nyoman Jampel; Made Candiasa; Muhammad Rey Dafa Ahmadi (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: Equitable access to education is a fundamental prerequisite for human capital development and social justice in Indonesia. This study aims to evaluate the effectiveness of education equity policies under the administration of President Prabowo Subianto, focusing on programs such as Sekolah Rakyat, the Indonesia Smart Program (PIP), and the Frontline Teacher and School Initiatives (GGD/SGD). Method: Employing a qualitative approach through library research, the study systematically reviews secondary data from scholarly literature published in the last five years, government policy documents, and reports from national and international institutions, including UNICEF and UNESCO. The analysis was conducted through thematic coding, synthesis of findings, and evaluative assessment using an input–output–outcome framework. Results: The findings reveal that affirmative programs have significantly expanded access to education, particularly in frontier, outermost, and underdeveloped (3T) regions, as well as for marginalized groups. However, persistent challenges remain in the uneven distribution and quality of teachers, inadequate physical and digital infrastructure, limited digital literacy, and policy approaches that are still largely top-down and insufficiently responsive to local contexts. These issues hinder the achievement of truly inclusive and high-quality education. Novelty: The key contribution of this study lies in its integrative perspective that combines structural (infrastructure), technological (digital platforms), human resource (teachers), and normative (human rights-based) dimensions. By advancing adaptive, evidence-based, and participatory strategies, this study provides a comprehensive framework for reshaping education policy in Indonesia toward greater inclusivity and equity.